2018
DOI: 10.1080/03067319.2018.1554743
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cocaine use patterns in the Brazilian Capital by wastewater-based epidemiology

Abstract: The levels of cocaine (COC) and its metabolites benzoylecgonine (BE) and cocaethylene (COE) in wastewater samples from Brasilia, Brazil, were determined using liquid chromatography coupled to hybrid quadrupole-time-offlight mass spectrometry. The former metabolite was used to estimate cocaine consumption using a country-tuned correction factor that considers BE excretion rates for different routes of administration as well as the fraction of crack users in Brazil. A day-today analysis during a week indicates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
4
14
1
Order By: Relevance
“…However, just a few previous studies for WBE of illicit drugs consumption using POCIS sampling were reported ( Baz-Lomba et al, 2017 ; Harman et al, 2011 ) and none of these studies evaluated the consumption of THC, the most commonly used illicit drug of abuse ( UNODC, 2021 ). Particularly in Brazil, only composite sampling was reported, with short-term evaluations, for COC ( da Silva et al, 2018 ; Maldaner et al, 2012 ; Sodré et al, 2018 ). In this study, a sampling campaing of almost a whole year was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, just a few previous studies for WBE of illicit drugs consumption using POCIS sampling were reported ( Baz-Lomba et al, 2017 ; Harman et al, 2011 ) and none of these studies evaluated the consumption of THC, the most commonly used illicit drug of abuse ( UNODC, 2021 ). Particularly in Brazil, only composite sampling was reported, with short-term evaluations, for COC ( da Silva et al, 2018 ; Maldaner et al, 2012 ; Sodré et al, 2018 ). In this study, a sampling campaing of almost a whole year was applied.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of COC in Brazilian cities was previously estimated, using 24 h composite sampling performed over 1–8 days ( da Silva et al, 2018 ; Maldaner et al, 2012 ; Sodré et al, 2018 ). These studies estimated higher consumptions of COC, from 700 mg day −1 1000 inh −1 to 6229 mg day −1 1000 inh −1 , with the latter referring to a composite sample collected in the last day of Carnival ( da Silva et al, 2018 ). Important to note that POCIS sampling provides an average concentration over the sampling period and is less affected by point variation in the use of a given drug.…”
Section: Resultsmentioning
confidence: 99%
“…Drug abuse, especially with licit or illicit drugs, continues to grow worldwide and Brazil represents a large share [12,14]. Consequently, anesthesiologists may be involved in the care of patients under the acute and chronic influence of a myriad of substances.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in cocaine loads was also observed during the Independence Day in US (Foppe et al, 2018), the Easter holiday in France (Thiebault et al, 2019), the Chinese National Day (Zhang et al, 2019), and the Brazilian Carnival (da Silva et al, 2018). Lai et al, 2013a) and Huerta-Fontela et al (2008) found that cannabis and cocaine use on Christmas and New Year's Eve increased in urban areas of Australia and Spain, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…Lai et al, 2013a) and Huerta-Fontela et al (2008) found that cannabis and cocaine use on Christmas and New Year's Eve increased in urban areas of Australia and Spain, respectively. The concomitant use of cocaine and alcohol was assessed by da Silva et al (2018) through the high content of cocaethylene in a wastewater sample collected during the 2018 Carnival Holiday in Brazil. The authors suggested that cocaine use could be even higher, as the ingestion of ethanol with cocaine leads to the excretion of cocaethylene instead of benzoylecgonine, the main metabolite used to estimate consumption.…”
Section: Introductionmentioning
confidence: 99%